2018
DOI: 10.1007/s40195-018-0790-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Microstructure and Mechanical Properties of the Modified 718 Alloy

Abstract: M718 alloy with an extra high Mo content of 7.50 wt% which reduced Nb addition and increased Al and Ti additions within the composition specifications of 718 alloy has been designed to increase the service temperature of 718 alloy. And the effect of the heat treatment on the microstructure and mechanical properties of M718 alloy has been investigated in this study. The results showed that Laves phase precipitated on the grain boundaries of M718 alloy instead of d-Ni 3 Nb phase in 718 alloy, and c 00 and c 0 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Moreover, the UTS (1651 MPa) for the SAD sample is higher than that reported by Ran et al (1488.98 MPa), [10] Chen et al (1635 MPa), [11] Zhu et al (1404 MPa), [28] and Han et al (1479 MPa). [29] Meanwhile, the FE of the SAD sample is higher than or closes to the previously reported value. Table 1 shows that the average microhardness (AMH) values of SDA and SAD samples are 497 AE 17 and 539 AE 12 HV, respectively.…”
Section: Mechanical Propertiessupporting
confidence: 78%
“…Moreover, the UTS (1651 MPa) for the SAD sample is higher than that reported by Ran et al (1488.98 MPa), [10] Chen et al (1635 MPa), [11] Zhu et al (1404 MPa), [28] and Han et al (1479 MPa). [29] Meanwhile, the FE of the SAD sample is higher than or closes to the previously reported value. Table 1 shows that the average microhardness (AMH) values of SDA and SAD samples are 497 AE 17 and 539 AE 12 HV, respectively.…”
Section: Mechanical Propertiessupporting
confidence: 78%
“…There are extensively experimental investigations on Ti–Nb–Zr RMEAs, ,, Ti–Nb–Zr–Ta, ,,, Ti–Nb–Zr–Mo, , and Ti–Nb–Zr–Hf–Ta , RHEAs. The Sn can restrain the formation of the α″ phase and ω phase and alter the mechanical properties of Ti alloys. Alternatively, Sn has a strong interaction with other elements, and it can also reduce the density and increase the effect of solid solution strengthening of alloys . Hence, in our current work, we systematically investigate the elastic moduli and mechanical properties of Ti–Nb–M (M = Zr, Mo, Sn, Ta) RMEAs.…”
Section: Introductionmentioning
confidence: 99%
“…52−54 Alternatively, Sn has a strong interaction with other elements, and it can also reduce the density and increase the effect of solid solution strengthening of alloys. 55 Hence, in our current work, we systematically investigate the elastic moduli and mechanical properties of Ti−Nb−M (M = Zr, Mo, Sn, Ta) RMEAs. Furthermore, the ratio of alloying elements in RMEAs is abundant according to extensive experimental findings.…”
Section: Introductionmentioning
confidence: 99%
“…Low [ 17 ] concluded that heat treatments that dissolve intermetallic components and eutectic phases would eliminate the possibility of liquefaction at lower temperatures and improve crack resistance. Han [ 18 ] concluded that thermal cracking occurs during the solidification of molten metal under laser heating and that the crack length can be reduced by decreasing the heat input. Keivanloo [ 19 ] found that reducing the cooling rate reduced residual stresses and decreased crack sensitivity.…”
Section: Introductionmentioning
confidence: 99%